Regulation of muscle protein metabolism by nutrition and exercise - Satoru Ato; Satoshi Fujita (Japanese Society of Physical Fitness and Sports Medicine, 2017)
Skeletal muscle is an essential tissue that regulates glucose metabolism and locomotive ability. Therefore, gaining skeletal muscle mass is important for maintaining or improving health as well as athletic sport performance. Over the past decade, resistance exercise has been shown to be the most effective method for gaining muscle mass. Acute resistance exercise increases muscle protein anabolism, and repeated training induces protein accumulation and muscle hypertrophy. Similarly, protein anabolism by nutrition intake, particularly protein and amino acid ingestion, is important for regulating skeletal muscle mass. Moreover, recent studies have indicated that a combination of resistance exercise and nutrition intake augments the anabolic effect more than exercise and/or nutrition intake alone. In this review, we discuss the mechanism underlying protein anabolism based on exercise and nutrition intake, as well as recommendations for optimizing protein anabolism by each stimulus based on the latest findings. Finally, recent evidence related to the cumulative effect of resistance exercise in combination with nutritional supplements on muscle protein metabolism is discussed.